Pulmonary artery stenosis in Takayasu disease mimicking pulmonary embolism on perfusion lung scan: A case report - Sebbar, Chaimae; Hiroual, Soufiane; Kouassi, Nathalie; Bsiss, Mohamed Aziz; Matrane, Aboubaker (Frontiers in Nuclear Medicine, 2023)
Lung scan is an accurate and noninvasive tool for evaluating the distribution of lung perfusion. We present a rare case of total absence of perfusion on lung scan to the right lung with two contralateral defects due to severe occlusion of the right pulmonary artery, as well as segmental arteries in the left lung in a young female woman diagnosed with Takayasu Arteritis. We highlight the similarities of the findings between pulmonary arteritis in Takayasu disease and thromboembolic disease and the importance of careful interpretation of perfusion lung scan in order to avoid misdiagnosis that could endanger the patient’s life.